A study on the solvability of fractional integral equation in a Banach algebra via Petryshyn's fixed point theorem - Sukanta Halder; Deepmala; Cemil Tunç (Journal of Taibah University for Science)
This study focuses on the nonlinear fractional functional integral equation (FFIE) concerning the Riemann-Liouville operator. In certain weaker conditions, the authors demonstrate that the FFIE has a solution, which is defined within the Banach algebra [Formula: see text]. Our analysis relies on the Petryshyn's fixed point theorem and the notion of measure of non-compactness (MNC). In addition, our results include numerous authors' work under less restrictive conditions. Furthermore, we provide an illustrative example of fractional functional integral equations to support our proven results.